Aerosol Transport Modeling: The Key Link Between Lung Infections of Individuals and Populations - Darquenne, Chantal; Borojeni, Azadeh A.T.; Colebank, Mitchel J.; Forest, M. Gregory; Madas, Balázs G.; Tawhai, Merryn; Jiang, Yi (Frontiers in Physiology, 2022)
The recent COVID-19 pandemic has propelled the field of aerosol science to the forefront, particularly the central role of virus-laden respiratory droplets and aerosols. The pandemic has also highlighted the critical need, and value for, an information bridge between epidemiological models (that inform policymakers to develop public health responses) and within-host models (that inform the public and health care providers how individuals develop respiratory infections). Here, we review existing data and models of generation of respiratory droplets and aerosols, their exhalation and inhalation, and the fate of infectious droplet transport and deposition throughout the respiratory tract. We then articulate how aerosol transport modeling can serve as a bridge between and guide calibration of within-host and epidemiological models, forming a comprehensive tool to formulate and test hypotheses about respiratory tract exposure and infection within and between individuals.